The Effect of Need for Knowledge, Learning Self-Efficacy, and Collective Learning on Teachers' Satisfaction with Learning - Choori, Ali; Hoseini, Seyed Mohsen (Health Nexus, 2023)
The aim of this study was to investigate the effect of need for knowledge, learning self-efficacy, and collective learning on physical education teachers' satisfaction with learning. The study was conducted using a survey research design. The entire population of physical education teachers in the primary and secondary schools of Golestan totaled 575 individuals. Based on Cochran's formula, the sample size was estimated to be 231 physical education teachers, selected through stratified random sampling. The data collection instruments included four questionnaires: Need for Knowledge (Kazan, 2016), Learning Self-Efficacy (Artino, 2012), Collective Learning (Glassman, 2014), and Satisfaction with Learning (Lin et al., 2018). The validity and reliability of the questionnaires were confirmed. The collected data were analyzed using SPSS and SMART PLS statistical software, both descriptively and inferentially. The research findings indicated that need for knowledge does not have a significant effect on physical education teachers' satisfaction with learning. Similarly, the results showed that learning self-efficacy does not have a significant effect on physical education teachers' satisfaction with learning. Finally, the results of the research revealed that collective learning has a positive and significant effect on physical education teachers' satisfaction with learning. Considering these results, it is recommended to highlight the importance of knowledge for physical education teachers and to increase their self-efficacy in learning.